Turn-Taking Strategy as Gender Performance in EFL Classroom Interaction - Oktarini, Widya; Citraningrum, Dina Merdeka (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to uncover patterns of turn-taking strategy differences between male and female students, and how these differences affect their engagement and participation in classroom discussions. The study is expected to provide deeper insight into the gender-based interaction dynamics in foreign language classrooms, offering valuable contributions to the development of more inclusive teaching methods. This research is qualitative with descriptive approach. The subjects of this study are second-semester students of the English Education Program at Muhammadiyah University of Jember.There are 20 students who participated in this study. The result of the research reveals that there are some turn taking strategy used by male and female students including self-selection, speaker-selected, overlapping talk, backchannels and silent delay which are used dominantly by the female students. Several factors that influence the selection of turn-taking strategies include self-confidence, social gender roles, and the influence of the classroom environment. Women feel more empowered when the classroom provides equal opportunities for all students to speak. In conclusion, The evolving social gender influence in education allows women to participate more in EFL classroom and take more initiative in conversations, which are typically dominated by men.